Disrupting the TRIB3-SQSTM1 interaction reduces liver fibrosis by restoring autophagy and suppressing exosome-mediated HSC activation. Issue 5 (3rd May 2020) - Zhang, Xiao-Wei; Zhou, Ji-Chao; Peng, Dian; Hua, Fang; Li, Ke; Yu, Jiao-Jiao; Lv, Xiao-Xi; Cui, Bing; Liu, Shan-Shan; Yu, Jin-Mei; Wang, Feng; Jin, Cai-Cai; et al.
ABSTRACT: Impaired macroautophagy/autophagy is involved in the pathogenesis of hepatic fibrosis. However, how aberrant autophagy promotes fibrosis is far from understood. Here, we aimed to define a previously unrevealed pro-fibrotic mechanism for the stress protein TRIB3 (tribbles pseudokinase 3)-mediated autophagy dysfunction. Human fibrotic liver tissues were obtained from patients with cirrhosis who underwent an open surgical repair process. The functional implications of TRIB3 were evaluated in mouse models of hepatic fibrosis induced by bile duct ligation (BDL) or thioacetamide (TAA) injection. Human fibrotic liver tissues expressed higher levels of TRIB3 and selective autophagic receptor SQSTM1/p62 (sequestosome 1) than nonfibrotic tissues and the elevated expression of TRIB3 and SQSTM1 was positively correlated in the fibrotic tissues. Silencing Trib3 protected against experimentally induced hepatic fibrosis, accompanied by restored autophagy activity in fibrotic liver tissues. Furthermore, TRIB3 interacted with SQSTM1 and hindered its binding to MAP1LC3/LC3, which caused the accumulation of SQSTM1 aggregates and obstructed autophagic flux. The TRIB3-mediated autophagy impairment not only suppressed autophagic degradation of late endosomes but also promoted hepatocellular secretion of INHBA/Activin A-enriched exosomes which caused migration, proliferation and activation of hepatic stellate cells (HSCs), the effector cells of liver fibrosis. Disrupting the TRIB3-SQSTM1 interaction with a specific helical peptide exerted potent protective effects against hepatic fibrosis by restoring autophagic flux in hepatocytes and HSCs. Together, stress-elevated TRIB3 expression promotes hepatic fibrosis by interacting with SQSTM1 and interfering with its functions in liver-parenchymal cells and activating HSCs. Targeting this interaction is a promising strategy for treating fibroproliferative liver diseases. Abbreviations : 3-MA: 3-methyladenine; AAV: adeno-associated virus; ACTA2/α-SMA: actin, alpha 2, smooth muscle, aorta; BDL: bile duct ligation; BECN1/Beclin 1: beclin 1, autophagy related; CHX: cycloheximide; CQ: chloroquine; Edu: 5-ethynyl-2-deoxyuridine; ESCRT: endosomal sorting complexes required for transport; HSC: hepatic stellate cell; ILV: intralumenal vesicle; LAMP1: lysosomal-associated membrane protein 1; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MVB: multivesicular body; PIK3C3: phosphatidylinositol 3-kinase, catalytic subunit type 3; PPI: protein-protein interaction; SQSTM1/p62: sequestosome 1; TAA: thioacetamide; TEM: transmission electron microscopy; TGFB1/TGFβ1: transforming growth factor, beta 1; TLR2: toll-like receptor 2; TRIB3: tribbles pseudokinase 3